Pengaruh Budaya Organisasi, Komitmen Dan Akuntabilitas Pada Kinerja Lembaga Perkreditan Desa - Amanda, Lidya Ayu; Dharma Suputra, I D.G. (E-Jurnal Akuntansi; Vol 27 No 3 (2019), 2019)
This research was conducted at the Village Credit Institution (LPD) in Denpasar City. The number of samples taken was 70 respondents. This study uses saturated samples. Data collection is done through interviews, observation and questionnaires. The data analysis technique used is multiple linear regression. Based on the results of the analysis it can be stated that organizational culture directly influences the positive performance of LPDs in Denpasar City. Direct commitment has a positive effect on LPD performance in Denpasar City. Accountability directly influences positively on LPD performance in Denpasar City. The application of organizational culture, commitment and good accountability to the organization will trigger good performance in an organization. The role of the leader of the organization must motivate and provide direction to its employees the goal is to build organizational culture, commitment and accountability in each employee (individual) to achieve the target organization that the organization wants. Keywords : Organizational culture, commitment, accountability and performance